Правосуддя як спосіб відновлення справедливості: аналіз засобів здійснення - Андреєв, Д.В. (Альманах права, 2012)
В статті розглядається динамічний процес розвитку правосуддя, починаючи зі стародавнього «ефекту залякування» до області абстрактної свідомості, коли ефективність покарання полягає не в його видовищності, а перш за все у розумінні його невідворотності. Крім того в роботі досліджуються засоби здійснення
карного правосуддя. Особлива увага приділяється інституту реабілітації, як сукупності заходів, щодо поновлення особи в правах та юридичному статусі, які вона втратила. В статье рассматривается динамичный процесс развития правосудия, начиная от древнего «эффекта запугивания» до сферы абстрактного сознания, когда эффективность наказания заключается не в зрелищности, а прежде всего в осознании его неотвратимости. Кроме того в работе исследуются способы свершения уголовного правосудия. Особое внимание уделяется институту реабилитации, как сумме методов,
которые возобновляют лицо в правах и юридическом статусе, которые были утрачены. Тhe article explains the dynamic process of justice development, beginning from the ancient «intimidation effect» to the field of abstract consciousness when the effectiveness of punishment is not in its stages but above all in the sense of unavoidability of punishment. Thereby justice does not take any more public responsibility for violence and punishment is being transformed from the art of inflicting incredible suffering into synonymy of suspended rights. At the same time we research methods of criminal justice enforcement. The essential elements of criminal justice are sanction, rehabilitation and amnesty. Particular attention is paid to the institution of rehabilitation, as a set of measures to restore the rights of individuals and his legal status, which he lost. More often we deal with automatic rehabilitation when the rights of every convicted person are restored after serving punishment. It looks like «erasing» his guilt before society. But, in case of legal errors, mass repressions, the society makes amendments for the innocent with the help of amnesty or remission.